L'histoire de l'Inra, entre science et politique - Cornu, Pierre (éditions Quae, 2018)
Set up during the food crisis in the aftermath of the Second World War, France's National Institute for Agricultural Research (INRA) was founded on the notion that public scientific research into the management of life in all its multifarious forms would be of major importance for rebuilding France's position in the world. This book, based on original documentation and testimonies of the main protagonists, explores the 70 years of the institute's life, focusing on the interactions between science and politics.